HIGHER EDUCATION FUNDING IN THE CZECH REPUBLIC IN THE YEARS 2001-2011 - Jaromir Tichy (European Scientific Journal, ESJ, 2014)
This paper is focused on the financing of higher education and its present, very discussed changes, which go hand in hand not only with the adopted strategic document, White Paper on tertiary education, but also with the overall economic and social situation of the Czech Republic. Based on data prom Czech statistical office, Ministry of Education, Youth and Sport and the Eurostat databse which are copared according to the relation to the problem, the status of higher education in the national economy is deduced. The issue of public and private resources are also discussed. The aim of the paper is to summarize information related to the decission making regarding interconnection between tertiary education and national economy and the possibilities of financing of higher education. Work analyse the above mentioned contexts by quantifying the relationship between changes in total public expenditure on education in the Czech Republic and changes of GDP of the Czech Republic based on available sources.